Integrating Augmented Reality, Assemblr Edu, and Google Sites in Economics Learning to Improve High School Students' Critical Thinking Skills - Cahyo Apri Setiaji; Sugeng Eko Putro Widoyoko; Lusy Rahmawati; Tengku Maaidah binti Tengku A Razak (LP. Ma'arif Janggan Magetan, 2026)
The background of the research is the low critical thinking ability of high school students and the ongoing gap in research on the development of digital-based learning media. This research aims to develop high school students' critical thinking skills while integrating the augmented reality platform, assembler edu, and google sites into one three-dimensional learning media. This type of research is research and development which adopts the Borg and Gall approach. The research subject were 200 high school students from two different schools. Data collection techniques used interviews, observations, documentation studies, and tests. The media design was tested through validation tests, small trials, extensive trials, and large-scale trials. The data analysis technique used a multivariate T-test to measure the significance of the treatment and N-Gain scores to measure the effectiveness of the media. The results showed an increase in critical thinking skills in the pretest and posttest scores of 51%. The results of the multivariate T-test showed a significant increase before and after media implementation with a sig value of 0.000 <0.05. The N-Gain test showed a result of 0.84>0.7, meaning that the effectiveness of the learning media was in the High category. The responses of teachers and students to the learning media were 90% and 83% respectively, meaning that teachers and students very well received the media.Based on the analysis, it was concluded that the Auregos learning media can improve high school students' critical thinking skills. The implications of utilizing Auregos learning media can support the sustainable improvement of the quality of economics learning in high schools.